Reconstrucción de vías catabólicas de hidrocarburos aromáticos policíclicos a partir de metagenomas de consorcios bacterianos aislado de suelos, región Loreto - Rodriguez Mashacuri, Hicler Napoleon (2023)
Microorganisms are subjected to intense research for various purposes, and metagenomic studies are fundamental supports to respond to many problems. The main objective of this research was to reconstruct the catabolic pathways of Polycyclic Aromatic Hydrocarbons (PAHs) present in the Metagenomes of Bacterial Consortia isolated from soils. The samples were collected from the Cuenca Alta Río Itaya Conservation Concession Area (CCCARI), the bacterial consortia were obtained by filtration and cultivated for 30 days in MSM enriched with PAHs. Then, metagenomic DNA was purified, libraries were prepared, and sequencing was performed on the Illumina NextSeq™ 550 platform. The metagenomic sequences obtained were processed using the MG-RAST server. The results indicated that the soil was characterized by having a texture: loam, extremely acidic pH (4.2). The diversity analysis revealed 108 species that degrade PAHs, with a predominance of bacteria (>99.80%), and 31 genes and their amino acid sequences that act in the different stages of pyrene catabolism were identified. Complete reconstruction of the Pyrene catabolic pathway based on the identified genes. Finally, the results indicated that the bacterial diversity present in the soil, when subjected to stress, are adaptable to different environments.